Anti-Protein-Arginine Deiminase 4 IgG and IgA Delineate Severe Rheumatoid Arthritis - Laura Martinez-Prat; Victor Martinez-Taboada; Cruz Santos; Marcos Lopez-Hoyos; Michael Mahler (Diagnostics, 2022)
There is a strong need for biomarkers of rheumatoid arthritis (RA) in all phases of the patient’s journey and to enable the implementation of precision medicine strategies to improve patient care. The objective of this study was to evaluate the presence of anti-protein-arginine deiminase (PAD) 4 IgG and IgA in the sera of RA patients and disease controls, and to investigate their association with joint erosion and biological treatment use. Sera from 104 RA and 155 controls were tested for the presence of anti-PAD4 IgG and IgA using a new particle-based multi-analyte technology (PMAT). Information on the erosive disease and biological treatment use was available for 54 of the RA patients, who were also tested for anti-citrullinated protein antibodies (ACPA). An association between the autoantibodies and these clinical features was investigated. Anti-PAD4 showed sensitivity and specificity values of 25.0% and 94.2% for IgG and of 21.2% and 94.8% for IgA for RA, respectively. The levels of these antibodies were also significantly higher in RA patients vs. controls, in erosive RA vs. non-erosive disease, and in patients under biologics vs. patients that were not on this treatment regimen. The anti-PAD4 IgG and IgA levels were correlated (rho = 0.60, p < 0.0001), but individuals that were positive for only one of the two isotypes were also observed. Anti-PAD4 IgG and IgA are associated with severe RA, and they represent valuable biomarkers for prognosis prediction and patient stratification.